Green Hydrogen Value Chain in the Sustainability for Port Operations: Case Study in the Region of Valparaiso, Chile - Rodriguez-Machuca, P (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
The paper presents a complete value chain for the use of green hydrogen in a port facility. The main objective was to propose the sizing of the main components that make up green hydrogen to ensure the supply of 1 MWe in replacing the diesel generator. The energy demand required for the port was determined by establishing the leading small and large-scale conventional energy-consuming equipment. Hence, 60 kgH2 was required to ensure the power supply. The total electrical energy to produce all the hydrogen was generated from photovoltaic solar energy, considering three-generation scenarios (minimum, maximum and the annual average). In all cases, the energy supply in the electrolyzer was 3.08 MWe. In addition, the effect of generating in the port facility using a diesel generator and a fuel cell was compared. The cost of 1 kgH2 could be 4.09 times higher than the cost of 1 L of diesel, meaning that the output kWh of each system is economically similar. In addition, the value of electrical energy through a Power Purchase Agreement (PPA) was a maximum of 79.79 times the value of a liter of diesel. Finally, the Levelized Cost of Energy (LCOE) was calculated for two conditions in which the MWe was obtained from the fuel cell without and with the photovoltaic solar plant. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.